1966
DOI: 10.1021/i260018a016
|View full text |Cite
|
Sign up to set email alerts
|

Coke Formation on Silica-Alumina Cracking Catalysts

Abstract: The mechanism of coke formation on silica-alumina cracking catalysts was studied by analysis of cracking experiments with seven pure hydrocarbons at 445' C. and n-hexadecane at 500" C. under a variety of process conditions. Coke deposits were isolated from selected catalyst samples for infrared spectral examination. Aromatic skeletal vibrations were observed a t 1580 to 1590 cm.-' Although the cokes were low in hydrogen content, it was possible to identify -Ctlz, -CH3, and aromatic -CH groups by infrared absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…6 1 .oc Table 4 and Table 5. On most catalysts used in hydrocarbon reactions where coking is observed, olefins have been associated with coke formation (Viner and Wojciechowski, 1982;Eberly et al, 1966). On most catalysts used in hydrocarbon reactions where coking is observed, olefins have been associated with coke formation (Viner and Wojciechowski, 1982;Eberly et al, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…6 1 .oc Table 4 and Table 5. On most catalysts used in hydrocarbon reactions where coking is observed, olefins have been associated with coke formation (Viner and Wojciechowski, 1982;Eberly et al, 1966). On most catalysts used in hydrocarbon reactions where coking is observed, olefins have been associated with coke formation (Viner and Wojciechowski, 1982;Eberly et al, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of results both theoretical and experimental, have been summarized in a recent review by Butt[l]. Eberly et al [2] conducted a study of coke formation for cumene cracking in a fixed bed of silica-alumina catalyst. They found that coke formation was a complex function of the length of the cracking cycle and space velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Eberly et al (1966) studied the cracking of n-hexadecane on silica-alumina catalysts. The effects of cycle time and space velocity on the amount of carbon deposited were investigated.…”
Section: Jyh-ping Hsumentioning
confidence: 99%
“…Voorhies (1945), e.g., proposed a power law correlation between the amount of carbon deposited and cracking time; a diffusion control mechanism was invoked. This model has been tested for different operating conditions and feed-catalyst combinations by numerous investigators in the subsequent studies (see, e.g., Blanding, 1953;Rudershausen and Watson, 1954;Wilson and Den Herder, 1958;Eberly, et al, 1966;Noda et al, 1974;Noda et al, 1975). It has been found that Voorhies' model is essentially an empirical representation since the adjustable parameter in the model varies for different cases.…”
Section: Introductionmentioning
confidence: 99%